Analysis of application status of spinning industry robot (Innovative Applications of AI, 2024)
To foster the application and research of robots in the spinning industry, this paper provides a summary and analysis of their current status of use. It reviews the application of Automated Guided Vehicles (AGVs) and cone yarn stacking robots within intelligent logistics systems. Furthermore, it discusses the use of automatic winding carts, fine yarn splicing robots, and sliver packaging robots in intelligent spinning single-machine equipment. The paper also contemplates the future development prospects of robots in the spinning sector and examines the challenges they face. It posits that the application of robots in the spinning industry is still in its nascent stage, with the primary goal of bridging the gaps in fully automated production processes and enhancing the continuity and intelligence of spinning production as the future direction for spinning robots.